Immunologic glomerulopathies-diagnostic role of immunofluorescence study of renal biopsies - Pandey, Kaushlendra K.; Tiwari, Anjali; Agarwal, Asha (International Journal of Research in Medical Sciences, 2017)
Background: The kidney is a structurally complex organ that has evolved to subserve a number of important functions: excretion of the waste products of metabolism, regulation of body water and salt, maintenance of appropriate acid balance, and secretion of a variety of hormones and autacoids. Some clinical disorders affect more than one structure. In addition, the anatomic interdependence of structures in the kidney implies that damage to one almost always secondarily affects the others. Thus, severe glomerular damage impairs the flow through the peritubular vascular system, conversely, tubular destruction, by increasing interglomerular pressure, may induce glomerular atrophy. Thus, whatever the origin, there is a tendency for all forms of chronic renal disease ultimately to destroy all four components of the kidney, culminating in chronic renal failure and what has been called end-stage contracted kidneys. The functional reserve of the kidney is large, and much damage may occur before functional impairment is evident. The circulating immune complexes play a very major role in various types of glomerular nephropathies. Methods: The present study was conducted on renal biopsies referred to Pathology Department of G.S.V.M. Medical College, Kanpur and Regency Hospital Ltd., Kanpur. Frozen section of renal biopsy was taken for IF studies. Renal biopsy tissue was received in IF fluid containing Ammonium sulphate, N-ethyl malcimide, Magnesium sulphate. Results: The lgG class of immunoglobulins was found to be most fatal to the G13M, the 1gM and IgA were also found to cause glomerular damage. This mechanism was seen responsible for most cases of ICGN. In the present study, fluorescent study of renal biopsy tissue was also done using Hollande’s fixative and it was observed that a better diagnosis could be done when used with routine H & E and immunofluorescent studies. Conclusions: The immunofluorescence microscopy proved to be very useful and essential, for proper diagnosis and therapy of a renal disease. IFM comes out to be a very good indicator of the deposition site and class of immunoglobulin involved in the Immune-complex deposit.